Pengaruh Gender, Lingkungan Kerja, Pelatihan Profesional, Pertimangan Pasar Kerja, dan Persepsi Mahasiswa terhadap Profesi Akuntan Publik dan Minat menjadi Akuntan Publik - Handayani, Putri; Zanaria, Yulita; Darmayanti, Elmira Febri (Universitas Muhammadiyah Metro, 2023)
This study aims to analyze the influence of gender, work environment, professional training, labor market considerations, and students' perceptions of the profession of a public accountant on interest in becoming a public accountant. The population in this research is 268 respondents. The sampling technique in this research used a Purposive Sampling Technique using the Slovin Formula for respondents to obtain a sample of 95 respondents. The data in this study used SPSS version 25 with multiple linear regression analysis testing. The results of this study indicate that students' perceptions of becoming accountants have a partial effect on interest in becoming public accountants. However, Gender, Professional Training, and Labor Market Considerations do not have a partial effect on the Interest to Become a Public Accountant. Taken together the variables Gender, Work Environment, Professional Training, Labor Market Considerations, and Student Perceptions of the Public Accountant Profession simultaneously influence Student Interests to Become Public Accountants in Students of the Muhammadiyah Metro University Accounting Study Program